One flew over the cuckoo's nest : a novel - Kesey, Ken (Penguin classics., 2003)
A mordant, wickedly subversive parable set in a mental ward, the novel chronicles the head-on collision between its hell-raising, life-affirming hero Randle Patrick McMurphy and the totalitarian rule of Big Nurse. McMurphy swaggers into the mental ward like a blast of fresh air and turns the place upside down, starting a gambling operation, smuggling in wine and women, and egging on the other patients to join him in open rebellion. But McMurphy's revolution against Big Nurse and everything she stands for quickly turns from sport to a fierce power struggle with shattering results.